A DFT study on the C–H oxidation reactivity of Fe(iv)–oxo species with N4/N5 ligands derived from l-proline. Issue 4 (8th January 2021) - Lin, Jin; Sun, Qiangsheng; Sun, Wei
Abstract : The hydroxylation of hexane by two Fe IV O complexes bearing a pentadentate ligand (N5, Pro3Py) and a tetradentate ligand (N4, Pro2PyBn) derived from l -proline was studied by DFT calculations. Abstract : The hydroxylation of hexane by two Fe IV O complexes bearing a pentadentate ligand (N5, Pro3Py) and a tetradentate ligand (N4, Pro2PyBn) derived from l -proline was studied by DFT calculations. Theoretical results predict that both Fe IV O complexes hold triplet ground states. The hydrogen atom abstraction (HAA) processes by both Fe IV O species proceed through a two-state reactivity, thus indicating that HAA occurs via a low-barrier quintet surface. Beyond the conventional rebound step, the dissociation path is also calculated and is found to potentially occur after HAA.